2018
DOI: 10.3390/toxins10040157
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Toxin Contributes to Biofilm Formation among Staphylococcus aureus Wound Isolates

Abstract: Biofilms complicate treatment of Staphylococcus aureus (SA) wound infections. Previously, we determined alpha-toxin (AT)-promoted SA biofilm formation on mucosal tissue. Therefore, we evaluated SA wound isolates for AT production and biofilm formation on epithelium and assessed the role of AT in biofilm formation. Thirty-eight wound isolates were molecularly typed by pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (ST), and spa typing. We measured biofilm formation of these SA isolates in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…Although Tang J et al indicated that a single gene or subset of genes cannot be utilized as an indicator of biofilm production [23], In some other studies, traditional adhesion-associated genes including ebps, ica and fnbA were suggested to be positively associated with biofilm production [11,22]. Exotoxin gene lip and hla genes were also verified to contribute to biofilm formation [12,32]. Different from the above results, in this study, we first found that the fib, hlgv and lukED gene was positively correlated, while sei, sem and seo genes were negatively correlated with biofilm production of orthopedic S. aureus strains (Tables 2, and 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Tang J et al indicated that a single gene or subset of genes cannot be utilized as an indicator of biofilm production [23], In some other studies, traditional adhesion-associated genes including ebps, ica and fnbA were suggested to be positively associated with biofilm production [11,22]. Exotoxin gene lip and hla genes were also verified to contribute to biofilm formation [12,32]. Different from the above results, in this study, we first found that the fib, hlgv and lukED gene was positively correlated, while sei, sem and seo genes were negatively correlated with biofilm production of orthopedic S. aureus strains (Tables 2, and 3).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study conducted by our team [9], we collected and characterized the S. aureus isolates obtained from the orthopedic center of our hospital over a 2-year period. In consideration that genetic and phenotypic characteristics of bacteria strains are closely related to the biological and physiological properties [6,8,[11][12][13], we hypothesized that some of these characteristics might be associated with biofilm formation, and the association might be different between OM and non-OM isolates. Therefore, interested isolates from the previous study were included and divided into OM and non-OM isolates, biofilm production was measured using the crystal violet assay.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated expression of a-toxin in the USA300 clone and in historic human epidemic strains correlates with increased pathogenicity in mouse models of skin and soft tissue infection, pneumonia and sepsis (48,49). a-Toxin also plays a role in biofilm formation by clinical MRSA isolates (50). Moreover, LukED relies on the chemokine receptor CCR5 to kill T lymphocytes, macrophages and dendritic cells, as well as CXCR1 and CXCR2 to kill leukocytes (19,51).…”
mentioning
confidence: 99%
“…The elevated expression of atoxin in the USA300 clone and in historic human epidemic strains correlates with increased pathogenicity in mouse models of pneumonia and sepsis (Bubeck Wardenburg and Schneewind, 2008;DeLeo et al, 2011). a-Toxin also plays a role in biofilm formation by clinical MRSA isolates (Anderson et al, 2018). Moreover, LukED relies on the chemokine receptor CCR5 to kill T lymphocytes, macrophages and dendritic cells, as well as CXCR1 and CXCR2 to kill leukocytes Reyes-Robles et al, 2013).…”
Section: Introductionmentioning
confidence: 99%